Investigation On High Neutral Earthing Resistor Temperature When Islanded Generator Connected To Utility Grid - Abdullah, M. F. (2010)
Electricity supply to Universiti Teknologi PETRONAS (UTP) is provided by two generating units at gas district cooling (GDC) plant located in the campus. Under normal operation, UTP power system is operating in island mode and during emergency, it will be connected to utility grid of Tenaga Nasional Berhad (TNB). Each generating unit is grounded through neutral earthing resistor (NER). It has been observed that NER temperature become high when generator operating in parallel with the grid. Investigation reveals that triplen harmonics currents continuously flow through NER during island and parallel operation. Higher triplen harmonics currents are noticed during parallel operation as compared to island mode of operation. High NER temperature is caused by increase in triplen harmonics currents that flow through it. The above phenomena are described in this paper together with some proposed measures to overcome the problem.